Refractory Mullite Phase Enhancement in Silicon Carbide/Kaolin Composites - Safa Jasim; Shihab Zaidan; Enas Hadi (Journal of Applied Sciences and Nanotechnology, 2024)
Refractory ceramics were produced using silicon carbide (SiC) as the main component in combination with different weight percentages of Iraqi white kaolin (20%, 40%, 60% and 80%). Two different weight percentages of alumina (5% and 10%) were then added to each SiC-kaolin mixture. The samples were effectively mixed, molded, dried and fired at 1300 °C. The structural and physical properties were measured, including X-ray diffraction, apparent porosity, water absorption and thermal conductivity. X-ray diffraction showed that the addition of Al2O3 to the SiC-kaolin composite increased the mullite phase by interacting with the excess silica formed during the firing of kaolin or with the silica formed during the oxidation of SiC. The increase in kaolin content in the composite without alumina was accompanied by a decrease in physical properties, as the apparent porosity decreased from 30.17% to 17.95% and the water absorption from 16.31% to 7.07%. The addition of 80 wt.% kaolin led to a decrease in thermal conductivity from 35 to 15 W/m.K. The addition of 10 wt% Al2O3 also reduced the apparent porosity and water absorption to 13.85% and 5.33% respectively for the (SiC-20 wt% kaolin) sample. The apparent porosity and water absorption of the sample (SiC-80 wt% kaolin) with 10 wt% Al2O3 reached the lowest values of 9.44% and 3.55%, respectively. The thermal conductivity decreased from 15 to 12 W/m.K. This study found that adding alumina improves refractory efficiency due to its high melting point, making it ideal for high-temperature applications.